1986
DOI: 10.1152/ajpcell.1986.250.3.c517
|View full text |Cite
|
Sign up to set email alerts
|

Activators of protein kinase C inhibit sodium transport in A6 epithelia

Abstract: To evaluate the role of protein kinase C in sodium transport via amiloride-sensitive sodium channels, we studied the effect of activators of protein kinase C on short-circuit current in epithelia formed by A6 cells in culture. In A6 epithelia, short-circuit current is equivalent to net sodium transport and is blocked by low concentrations of amiloride added to the solution bathing the apical surface. After any of four different activators of protein kinase C [phorbol 12,13-dibutyrate (20 ng/ml), phorbol 12-myr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 17 publications
7
29
0
Order By: Relevance
“…The lack of effect of amiloride on the PMA-induced ISC indicated that this current was not via the amiloride-sensitive sodium channel and that, furthermore, PMA inhibited the preexisting amiloride-sensitive sodium transport. These observations correspond to those made by Yanase and Handler (1986) who concluded that activators of PKC inhibit sodium transport and stimulate an amiloride-resistant ISC' which most likely represents basolateral to apical chloride transport.…”
Section: Measurement Of the Basolateral Membrane Capacitancesupporting
confidence: 90%
See 2 more Smart Citations
“…The lack of effect of amiloride on the PMA-induced ISC indicated that this current was not via the amiloride-sensitive sodium channel and that, furthermore, PMA inhibited the preexisting amiloride-sensitive sodium transport. These observations correspond to those made by Yanase and Handler (1986) who concluded that activators of PKC inhibit sodium transport and stimulate an amiloride-resistant ISC' which most likely represents basolateral to apical chloride transport.…”
Section: Measurement Of the Basolateral Membrane Capacitancesupporting
confidence: 90%
“…Several studies have shown that direct PKC stimulation and hormones acting via PKC stimulation decrease the activity of the amiloride-sensitive epithelial sodium channel and hence sodium reabsorption in the cortical collecting duct and A6 epithelia (Yanase and Handler, 1986;Hays et al, 1987;Ling and Eaton, 1989;Ling et al, 1992;Takeda et al, 1994;Frindt et al, 1996). In the present study, we confirm that PKC stimulation by PMA blocks the amiloride-sensitive short circuit current in A6 epithelia while it stimulates an amiloride-resistant ISc, which most likely corresponds to Cl secretion ( Figure 1; Yanase and Handler, 1986).…”
Section: Effect Of Pkc Stimulation On Sodium Reabsorptionsupporting
confidence: 84%
See 1 more Smart Citation
“…A PKC-dependent AQP2 retrieval from apical membrane of principal cells has also been observed (56). Other studies suggest that calcium/PKC-coupled signaling not only inhibits water flow but also inhibits Na ϩ absorption and K ϩ secretion in the collecting ducts (26,46,59).…”
Section: Discussionmentioning
confidence: 87%
“…The effects of PKC on amiloride-sensitive Na ϩ transporting pathways were even more complex and diverse. Activation of PKC greatly diminished Na ϩ transport in A6 cells (52,53) and in the LLC-PK1 epithelial cell line (54). PKC also attenuated the activity of purified renal amiloride-sensitive sodium channels (55).…”
Section: Rt-pcr and Western Blot Detection Of Pkc Isozymes-rt-mentioning
confidence: 99%